An Environmental Theory Approach to Predicting Treatment-Seeking Behavior for Depression Among Indonesian Adolescents - Prihatmono, Ignatius Gonggo (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Depression is an increasingly prevalent mental health issue among Indonesian adolescents. According to the 2018 Basic Health Research (Riskesdas), the prevalence of emotional mental disorders among individuals aged 15 years and above has shown a significant increase. Many adolescents experience depressive symptoms but do not seek medical help due to social stigma and limited access to mental health services. Environmental factors—such as academic pressure, family conflict, social media exposure, and economic conditions—play a crucial role in shaping help-seeking behavior for mental health services. This study aims to explore how environmental theory can be applied to predict help-seeking behavior among adolescents experiencing depression in Indonesia. A qualitative literature review method was employed to analyze environmental factors that influence adolescents’ decisions to seek mental health services. Data were obtained from scientific journals, research reports, and publications from relevant health organizations. The findings indicate that help-seeking behavior among adolescents is strongly influenced by social, cultural, economic, and health policy factors. Social stigma and cultural norms remain major barriers to seeking professional support. Additionally, limited mental health services, particularly in rural areas, further hinder access to care. However, with the advancement of technology, telemental health services offer a promising solution to enhance accessibility and reduce stigma surrounding mental health. In conclusion, effective strategies to improve help-seeking behavior among adolescents should include strengthening mental health literacy, reducing stigma, and expanding access to digital-based services. Active involvement of families, schools, and government institutions is essential to creating an environment that supports adolescent mental health in Indonesia.